Safety and Tolerability of Esomeprazole in Children With Gastroesophageal Reflux Disease. (July 2015) - Gilger, Mark A.; Tolia, Vasundhara; Vandenplas, Yvan; Youssef, Nader N.; Traxler, Barry; Illueca, Marta
ABSTRACT: Objectives: To evaluate safety, tolerability, and symptom improvement with once-daily esomeprazole in children with endoscopically proven gastroesophageal reflux disease (GERD). Patients and Methods: In this 8-week, multicenter, randomized, uncontrolled, double-blind study, children ages 1 to 11 years were stratified by weight to receive esomeprazole 5 or 10 mg (children < 20 kg) or 10 or 20 mg (children ≥ 20 kg) once daily. Safety and tolerability was assessed by evaluating adverse events (AEs; both treatment- and non-treatment-related AEs) and changes from baseline in medical history, physical examinations, and clinical laboratory tests. Investigators scored symptom severity every 2 weeks using the Physician's Global Assessment (PGA). Patients' parents rated GERD symptoms of heartburn, acid regurgitation, and epigastric pain (none to severe, 0–3) at baseline (based on past 72 hours) and daily (from past 24 hours). Results: Of 109 patients randomized, 108 had safety data. AEs were experienced by 68.0% and 65.2% of children <20 kg receiving esomeprazole 5 and 10 mg, respectively, and 83.9% and 82.8% of children ≥20 kg receiving esomeprazole 10 and 20 mg, respectively, regardless of causality. Overall, only 9.3% of patients reported 13 treatment-related AEs; the most common were diarrhea (2.8% [3/108]), headache (1.9% [2/108]), and somnolence (1.9% [2/108]). Vomiting, a serious AE in 2 patients, was not judged by the investigator to be related to treatment. At the final visit, PGA scores improved significantly from baseline ( P < 0.001). Of 58 patients with moderate to severe baseline PGA symptom scores, 91.4% had lower scores by the final visit. GERD symptom scores were significantly improved from baseline to the final week of the study in all of the treatment groups ( P < 0.01) Conclusions: In children ages 1 to 11 years with endoscopically proven GERD, esomeprazole (at daily doses of 5, 10, or 20 mg) was generally well tolerated. The frequency and severity of GERD-related symptoms were significantly reduced during the active treatment period.